2021
DOI: 10.1177/0145482x211000963
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment and Employment for Individuals with Visual Impairments

Abstract: Higher educational attainment is known to be associated with lower unemployment rates and higher employment rates and lifetime earnings for the general population (Tamborini et al., 2015; U.S. Bureau of Labor Statistics, 2019b, 2019a). A substantial amount of research has also supported the importance of higher education for employment outcomes of people with visual impairments (i.e., those who are blind or have low vision;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…However, the earnings gap decreased when education level was considered, contrary to Kirchner and Peterson's (1980) findings. Even though higher education levels for people with visual impairments are associated with a greater likelihood of employment (McDonnall & Tatch, 2021) and higher earnings, as documented in this study and others (e.g., Bell, 2010;Estrada-Hernandez, 2008), they do not entirely close the earnings gap between people with and without visual impairments.…”
Section: Discussioncontrasting
confidence: 65%
“…However, the earnings gap decreased when education level was considered, contrary to Kirchner and Peterson's (1980) findings. Even though higher education levels for people with visual impairments are associated with a greater likelihood of employment (McDonnall & Tatch, 2021) and higher earnings, as documented in this study and others (e.g., Bell, 2010;Estrada-Hernandez, 2008), they do not entirely close the earnings gap between people with and without visual impairments.…”
Section: Discussioncontrasting
confidence: 65%
“…Individuals with VI have greater difficulty accessing food due to transportation barriers, lack of accessible grocery stores, difficulty preparing food, and affording nutritious food ( 27 ). Overarching disparities in employment, education and income also contribute to the financial strain of affording food as there are competing interests such as affording housing and medical care ( 28 , 29 , 30 ). In addition to VI contributing to food insecurity in older adults, a second bi-directional relationship likely also exists with food insecurity and poor nutrition contributing to the progression and development of various ophthalmic diseases ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having the skills to accommodate VI will also be essential to pursue additional education. Education has been positively associated with employment for persons with VI [11][12][13]. Increasing education will likely expand vocational options for persons with multiple health and disability issues as this group has a substantially lower educational level than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews concerning employment among persons with VI found education was positively associated with employment [11,12]. More recent studies supported this link [13,14]. Consequently, people with VI and less education appear at a disadvantage in becoming employed.…”
Section: Introductionmentioning
confidence: 99%